Analisis Kualitas Pelayanan Mc Donald’s Kota Serang - Kamila Cahya; Okvin Mulia; Syamsul Hidayat (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The increasingly fierce competition in the food business currently causes food companies to always improve the quality of their food and services. McDonald's is a company that operates in the services and products sector that sells fast food. Fast food is in great demand by various groups because of how easy it is to get it. Mc Donald's is a fast food restaurant that is very popular with consumers in various regions. This restaurant serves a variety of ready-to-eat foods that offer various other aspects such as service, price, and so on. This is expected to satisfy consumers. The purpose of this research is to determine the characteristics of consumers who often or have used services at Mc Donald's, to find out consumer satisfaction with the products provided by this Mc Donald's restaurant. Good service quality, affordable prices, attractive promotions and strategic locations are very important in building a franchise. This research aims to understand the quality of service provided by McDonald's restaurants by examining five dimensions of service quality, namely tangible, reliability, responsiveness, assurance and empathy.